Karsinoma Pelvis Renis dan Ureter di Jakarta: Karakteristik dan Faktor Risiko - YEVRI ZULFIKAR; RAINY UMBAS; CHAIDIR A MOCHTAR (Indonesian Journal of Cancer, 2010)
To study the characteristics,diagnosis and role of upper urinary tract stone as risk factors of renal pelvis and ureter malignancy. Data were collected from medical record of Urology Clinic Ciptomangunkusumo Hospital and Dharmais Cancer Hospital, Jakarta during the period between January 1995 and December 2009. The clinical factors which were studied are age, gender, symptoms, history of stone disease, imaging, histopathology , primary lesions of the tumor, and stage. There were 42 renal pelvis and ureter carcinoma patients during 15 years period. With mean age of 53.5 years (range 33 74). There were 54.8% cases associated with stone disease. The most common histopatology was Transitional Cell Carcinoma (TCC) (47.6%). Ninety two point nine percent cases with Squamous Cell Carcinoma (SCC) are associated with stone or history of operation for stone removal. Symptom of flank tumor occurred in 61.0 % patients, flank pain 58.5 %, and hematuria 53.7 %. Only 71.4 % of cases were detected pre operatively. Pre operative imaging detection were 89.3%, 53.8%, 20.7% for CT Scan USG and IVU respectively . Fifty two point five percents of patients were found on Stage IV and 47.8 % of these patients were associated with stone disease. Most of patients with renal pelvis and ureter carcinoma were associated with stone disease, especially in patients with SCC tumors. There are still some problems in detecting these tumors especially in early stage.